Substance Pressure Material Module-el Discovery Learning to Improve the Critical Thinking Ability of Middle School Students - Rohmah*, Seffy Mufidatur; Jumadi, Jumadi; Nurohman, Sabar; Borhan, Mohamad Termizi (Universitas Syiah Kuala, 2024)
The low critical thinking ability of Indonesian students is known based on the acquisition of PISA and TIMMS assessments with positions in the lower middle rankings. The lack of teaching materials that facilitate the improvement of critical thinking skills is one of the contributing factors. The purpose of this research and development is to produce a substance stress module to improve the critical thinking skills of junior high school students using model discoverylearning. The development model used is 4-D, with stages including define(definition), design(planning), develop(development), and disseminate(spread). Data collection was carried out through a literature review, validation assessment, and e-module practicality response questionnaires. Data collection was carried out through instruments in the form of validation assessment sheets by practitioners and student practicality response questionnaire sheets. Practitioners assess the validity of teaching materials, while their practicality is assessed by students. The results of the material validation were 89.2% (very valid), the media validation was 90% (very valid), the student practicality questionnaire was 76.2% (practical), and the N-gain score was 0.46. These results indicate that the science modules developed are valid and practical for use in science learning